School Choice and Conflict Narratives: Representative Bureaucracy at the Street Level in East Jerusalem. Issue 4 (April 2020) - O'Connor, Karl; Larkin, Craig; Nasasra, Mansour; Shanks, Kelsey
In representative bureaucracy research, the dominant view holds that passive representation leads to active representation. Much of the research to date has focused on the conditions that influence this process. In this research, we argue that more attention needs to be paid to the manifestation of active representation, rather than simply its presence. We find that although passive representation may indeed lead to active representation, the nature of this active representation is interpreted differently by those sharing a primary identity. We use the lens of representative bureaucracy theory, and Q Methodology, to understand how street-level bureaucrats in East Jerusalem use their discretion within the education system of a contested society.